1991
DOI: 10.1007/bf00315688
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death and paroxysmal autonomic dysfunction in stiff-man syndrome

Abstract: Two women with typical stiff-man syndrome (SMS) developed increasingly frequent attacks of muscle spasms with severe paroxysmal autonomic dysfunctions such as transient hyperpyrexia, diaphoresis, tachypnea, tachycardia, pupillary dilation, and arterial hypertension. Autoantibodies to GABA-ergic neurons were identified in the serum of both patients and in the cerebrospinal fluid of one. Both died suddenly and unexpectedly. General autopsy did not reveal the cause of death. Neuropathological studies revealed per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
6

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 32 publications
0
41
0
6
Order By: Relevance
“…Autoimmune mechanisms have been proposed to underlie the autonomic symptoms in several disorders including Guillain-BarrC syndrome [37], diabetes [38-401, stiff-man syndrome [41], Chagas' disease [42], idiopathic autonomic neuropathy [43], cholinergic dysautonomia [44- neurological disorders are known to be due to genetic or antibody-mediated ion channelopathies; to our knowledge, the present study is the first demonstration that an autonomic disorder can be caused by an antibody-mediated interference with specific ion channel function.…”
Section: Functional Consequences Of Down-regulation Of Vgccsmentioning
confidence: 99%
“…Autoimmune mechanisms have been proposed to underlie the autonomic symptoms in several disorders including Guillain-BarrC syndrome [37], diabetes [38-401, stiff-man syndrome [41], Chagas' disease [42], idiopathic autonomic neuropathy [43], cholinergic dysautonomia [44- neurological disorders are known to be due to genetic or antibody-mediated ion channelopathies; to our knowledge, the present study is the first demonstration that an autonomic disorder can be caused by an antibody-mediated interference with specific ion channel function.…”
Section: Functional Consequences Of Down-regulation Of Vgccsmentioning
confidence: 99%
“…Finally, patients may suffer paroxysmal autonomic dysfunction, dysphagia from esophageal dysmotility, and seizures. 6,7 Case reports have demonstrated an association between SPS and diabetes, but a major breakthrough in understanding the pathophysiology of SPS came in 1988 when Solimena et al identified antibodies against glutamic acid decarboxylase (GAD) in the serum and cerebrospinal fluid (CSF) of a patient with SPS and diabetes.8 GAD is the rate-limiting enzyme involved in the synthesis of γ-aminobutyric acid (GABA), the major inhibitory neurotransmitter in the CNS (Figure 2). The hypothesis that the loss of GABA-signaling in the CNS is the cause of SPS was supported by magnetic resonance spectroscopy showing a selective reduction in GABA in the sensorimotor cortex of patients with SPS.…”
Section: Discussionmentioning
confidence: 99%
“…A progresszív encephalomyelitis rigiditással súlyos, rapid lefolyású kórkép. Spazmusrohamok vagy gyógyszermeg-vonás után a kialakuló paroxizmális autonóm dysfunctióhoz társuló hirtelen halálról is beszámoltak [32]. Fontos fi gyelembe venni a társuló betegségeket, atípusos és a-GAD-antitest negatív esetekben paraneoplasiára kell gondolnunk.…”
Section: Prognózisunclassified